2021
DOI: 10.5455/aim.2021.29.51-58
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Digital Healthcare Platforms During the COVID-19 Pandemic: the Consumer Perspective

Abstract: Background: The spending on digital healthcare solutions is estimated to reach EUR 232 billion by 2025. Digital healthcare platforms are making transformative changes to conventional healthcare processes which can provide many beneficial improvements for both citizen and government provision to society. These benefits are obvious during pandemics such as Covid-19, when most healthcare services are offered through digital means. Objective: The objective of this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 37 publications
2
18
0
2
Order By: Relevance
“…Furthermore, healthcare transformation programme as a part of vision 2030 which included rapid digitalization of healthcare system has proved to be beneficial in delivering the healthcare services as there was a significant increase in the deployment of various mHealth application and also increase in the number of mHealth users [ 4 ]. However, studies [ 5 8 ] have identified issues in mHealth implementation in Saudi Arabia such as lack of awareness of mHealth among the citizens, and lack of facilitating conditions. In addition, varying levels of accessibility, utilization, and perceptions of digital health technologies were identified across different population groups in Saudi Arabia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, healthcare transformation programme as a part of vision 2030 which included rapid digitalization of healthcare system has proved to be beneficial in delivering the healthcare services as there was a significant increase in the deployment of various mHealth application and also increase in the number of mHealth users [ 4 ]. However, studies [ 5 8 ] have identified issues in mHealth implementation in Saudi Arabia such as lack of awareness of mHealth among the citizens, and lack of facilitating conditions. In addition, varying levels of accessibility, utilization, and perceptions of digital health technologies were identified across different population groups in Saudi Arabia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Information quality is the ability of information to satisfy users' information needs (Alshikhi & Abdullah, 2018). Information quality includes reference to the accuracy, timeliness, and relevance of the information provided to users (Alharbi, 2021). According to Xie et al, (2017) information quality is information that can provide knowledge for users to find out the information needed.…”
Section: Quality Of Information On Purchase Decisionsmentioning
confidence: 99%
“…Trust can be interpreted as a person's willingness towards others with the hope and belief that others can give important actions for the giver, regardless of their abilities (Alotaibi et al, 2019). Using telemedicine is based on trust where trust is a person's belief that can be measured from a social perspective, which mainly concerns the doctor-patient relationship (Alharbi, 2021). Patient trust is defined as beliefs about expectations that are based on expertise, privacy, confidentiality, and reliability from experts ( Wu et al, 2021).…”
Section: The Effect Of Trust On Purchase Decisionsmentioning
confidence: 99%
“…Though the digitalization process has ramped up, studies [ 6 , 7 ] have identified issues such as lack of preparedness and awareness of eHealth among the citizens, which has affected the implementation of eHealth solutions in the country. A recent study [ 8 ] has highlighted that lack of facilitating conditions in relation to eHealth has affected the trust among healthcare consumers. Furthermore, there were issues identified in relation to the formulation of eHealth policies and implementing them, as disparities were identified among the various population groups in terms of accessibility, utilization, and perceptions of digital health technologies [ 9 ].…”
Section: Introductionmentioning
confidence: 99%